2021
DOI: 10.1186/s12888-021-03232-z
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and outcomes of group volunteer befriending with patients with severe mental illness: an exploratory mixed-methods study in Colombia

Abstract: Background Improving care for patients with severe mental illness in Latin America requires effective strategies that are low-cost. One such strategy is a volunteering scheme, referred to as befriending, which seeks to support the social integration of patients. Despite positive reports in other world regions, this intervention has not been studied in Latin America. Whilst befriending programmes commonly form patient-volunteer dyads, group arrangements may be an alternative with some benefits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 30 publications
(17 reference statements)
4
16
0
1
Order By: Relevance
“…Several studies acknowledge the importance of friendships for an individual's social inclusion process (Botero-Rodríguez et al, 2021 ; McConkey et al, 2021 ; Wilson et al, 2017 ). Such studies prove that people with intellectual disabilities, especially those with a higher degree of disability, have fewer friends and social relationships than people with a lower degree of disability (Robinson et al, 2020 ); thus, finding a network of friends to provide them with assistance is central and urgent.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies acknowledge the importance of friendships for an individual's social inclusion process (Botero-Rodríguez et al, 2021 ; McConkey et al, 2021 ; Wilson et al, 2017 ). Such studies prove that people with intellectual disabilities, especially those with a higher degree of disability, have fewer friends and social relationships than people with a lower degree of disability (Robinson et al, 2020 ); thus, finding a network of friends to provide them with assistance is central and urgent.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The relationship between a so-called normal individual and an intellectually disabled person provides benefits to both parties (Wilson et al, 2017 ). Socialisation improves personal health and well-being, and expanding the personal circle of friends can enhance social development (Botero-Rodríguez et al, 2021 ; Wilson et al, 2017 ; Zboja et al, 2020 ), and potentially foster greater social contact and improvements in the psychosocial domain (Wilson et al, 2017 ). On the other hand, volunteers develop a greater sense of self-care (Botero-Rodríguez et al, 2021 ; Morris et al, 2017 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial interventions that are low-cost and make use of a patient’s existing personal and social resources are an effective strategy to provide low-cost and effective health care for patients with severe mental illnesses in low-resource settings where there are often limited financial resources and trained professionals to provide specialized mental health services [ 1 – 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in DIALOG+, patients reported that it promoted empowerment and allowed for greater self-reflection and expression [ 12 ]. Befriending through volunteers was shown to lead to benefits such as reducing stigma and building relationships [ 4 , 13 ]. Family involvement interventions also were experienced positively by patients, providing a space conducive for shared learning to occur [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%